Attitude of Nursing Students toward People Living with Mental Disorder - Kinley Gyaltshen; Dawa Gyeltshen; Nima Dorji; Kuenzang Kuenzang; Nguldup Gyeltshen (Indian Journal of Psychiatric Nursing)
Background: Stigma held by health-care professionals toward people with mental illness can have serious negative impact on the quality of care provided by them. It is essential to adequately train the nursing students to develop favorable attitudes toward mental illness. In Bhutan, the level of stigma among student nurses remains understudied. Objective: The objective of this study is to investigate the attitudes of student nurses toward people with mental illness. Methods: It was a cross-sectional survey. A total population sampling technique was used. Two hundred and thirty-six student nurses completed a 40-item Community Attitudes toward Mentally Ill (CAMI) questionnaire to determine whether people with mental illness were viewed as “inferior;” deserving “sympathy;” perceived as a “threat” to the society or “acceptable” in the community. Independent t-tests and the analysis of variance were performed to determine the association of categorical variables with the CAMI. Results: Nursing students had favorable attitudes toward people with mental illness. The mean scores for the authoritarian (27.56 ± 3.95), benevolence (39.33 ± 3.71), social restrictiveness (21.51 ± 4.54), and community mental health ideology (37.29 ± 4.85) subscales reflected a positive attitude of student nurses. There was significant difference (F = 4.79, P < 0.01) only in the dimension of authoritarianism when CAMI subscales were compared according to the level (year) of the course. Conclusion: The study confirmed positive attitudes of student nurses toward people with mental illness. However, no significant difference in attitudes of student nurses according their level (year) of study underscores the need for revisiting current psychiatric curriculum and calls for further studies in the area.